2017
DOI: 10.1080/08997659.2016.1254121
|View full text |Cite
|
Sign up to set email alerts
|

Potential Reservoirs and Risk Factors for VHSV IVb in an Enzootic System: Budd Lake, Michigan

Abstract: Viral hemorrhagic septicemia virus genotype IVb (VHSV IVb) has caused major, sporadic fish die-offs in the Laurentian Great Lakes region of North America since 2005. Presently, factors affecting VHSV IVb persistence in enzootic systems are not well understood. Even with annual surveillance, the virus can go undetected for several years after an outbreak before again re-emerging, which suggests that the virus is maintained in the system either below detectable levels or in untested reservoirs. The aim of this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Throckmorton et al. (2017) likewise discovered no VHSV in cylindrical papershell mussels ( Anodontoides ferussacianus ) from Budd Lake, despite positive largemouth bass and Hyalellidae amphipods from that location. Researchers in Denmark tested for a VHSV‐II invertebrate reservoir in isopods, krill, and squid, but none were positive (Skall, Olesen, & Mellergaard, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Throckmorton et al. (2017) likewise discovered no VHSV in cylindrical papershell mussels ( Anodontoides ferussacianus ) from Budd Lake, despite positive largemouth bass and Hyalellidae amphipods from that location. Researchers in Denmark tested for a VHSV‐II invertebrate reservoir in isopods, krill, and squid, but none were positive (Skall, Olesen, & Mellergaard, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…It has been postulated that some invertebrates may harbor VHSV‐IVb, serving as possible reservoirs, including Hyalellidae amphipods (Throckmorton et al., 2017), Pontoporeiidae amphipods (e.g., Diporeia spp. ; Faisal & Winters, 2011), and an individual leech ( Myzobdella lugubris ) (Faisal & Schulz, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…We focused on Novirhabdoviruses of economic or ecological importance in North America: VHSV-IVb and IHNV-M genotypes. VHSV-IVb is of significant ecological concern in the Laurentian Great Lakes region where sporadic outbreaks have occurred over the past 17 years [31,65,66], thus there is tangible risk to all farmed fish in the region. But to date, VHSV-IVb has shown limited pathogenicity toward rainbow and brown trout [24,54], this could enable the disease to go undetected in a production setting.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, several different virus strains have been isolated from cultured and wild largemouth bass, such as ranavirus, VHSV, megalocytivirus and siniperca chuatsi rhabdovirus (Groocock, Grimmett, Getchell, Wooster, & Bowser, ; Ma et al, ; Mao, Wang, Chinchar, & Chinchar, ; Throckmorton et al, ). Among them, VHSV, a highly contagious fish pathogen, has caused serious economic damage to the production and quality of a wide range of fish species including but not limited to largemouth bass all over the world (Kim et al, ; Pereiro, Figueras, & Novoa, ; Throckmorton et al, ). Many wild fish have been reported to be carriers of VHSV, including olive flounder, silver pomfret and so on (Kim et al, ; Lee, Yun, Kim, Jung, & Oh, ), these VHSV‐positive fish had a major role in VHSV transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Here, the phylogenetic analysis based on the whole‐genome sequences and G gene sequences revealed that the VHSVLB2018 isolate belonged to genotype IVa, which is similar to the VHSV isolates from other fishes in Asia (Kim et al, ). Differently, a VHSV isolate of genotype IVb was detected from largemouth bass in the great lakes region in the United States and Canada (Kim & Faisal, ; Throckmorton et al, ). Since the first VHSV strain was isolated from farmed Japanese flounder in Japan (Takano, Nishizawa, Arimoto, & Muroga, ), many different strains of VHSV have been reported in a wide range of fish species in Asia.…”
Section: Discussionmentioning
confidence: 99%